The 'Heron': Nine steps for a past life. (May 2023) - Gilloch, Graeme
In Farewell to the Working Class, 1 (1982), a book dedicated to his wife Dorine, André Gorz (1923–2007) offers the reader 'Nine Theses for a Future Left'. Here, I borrow and play with this nomenclature for a series of reflections on the two volumes which constitute Gorz's most personal writings and which book-end, so to speak, his oeuvre: The Traitor and Letter to D. A Love Story . More precisely, this is a viewing of the former text through the lens of the latter. The 'steps' presented here are not those of a linear path and progression but rather, like steps in a dance, move backwards and forwards, turn and circle, trace and retrace ephemeral patterns. In following in such steps, I contrast Gorz's account of the self with another set of explicitly non- autobiographical autobiographical writings, those of the German Critical Theorist Walter Benjamin (1892–1940). Central to both writers is an understanding of particular traumatic experiences and past catastrophes, and an abiding concern with overcoming contemporary alienation through play and dance, love and eros.